Evaluation of the prevalence of and factors associated with laryngeal diseases among the general population. (7th July 2015) - Hah, J. Hun; Sim, Songyong; An, Soo‐Youn; Sung, Myung‐Whun; Choi, Hyo Geun
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Despite the high prevalence of voice disorders, the prevalence of laryngeal disease in the general population has not been determined using laryngoscopy. Factors considered associated with laryngeal disease have mostly been assessed using patient data or highly specific populations. We evaluated the prevalence of and associated factors with laryngeal diseases in the general Korean population. Study Design Cross‐sectional study. Methods We analyzed data from the Korea National Health and Nutrition Examination Survey for 19, 039 participants assessed between 2008 and 2011. The prevalence, subjective discomforts rates of, and odd ratios (demographics, life‐style factors, and diseases factors) for laryngeal disease were analyzed using simple and multiple logistic regression analyses, taking into account the complex sampling structure of the data. Results The top five laryngeal diseases in prevalence were laryngitis (3, 513/100, 000), vocal nodules (1, 487/100, 000), vocal polyp (404/100, 000), Reinke's edema (347/100, 000), and epiglottic cyst (296/100, 000). Prevalence of laryngeal disease was higher in males, whereas the rate of subjective voice complaints was higher in females. In the logistic regression analysis, gender was not associated with laryngeal diseases after adjusting for other factors. We observed a positive association between low body mass index (BMI) and vocal nodules, and between high BMI and laryngitis, smoking and epiglottic cyst/hyperkeratosis/laryngeal cancer, higher education level and vocal nodules, and allergic rhinitis and vocal nodules/laryngitis/epiglottic cyst. Conclusions The rate of subjective voice complaints and laryngeal disease co‐occurrence was low. This study provides more reliable information of laryngeal disease because it includes participants without subjective complaints. Level of Evidence 2b. Laryngoscope, 125:2536–2542, 2015